2019
DOI: 10.1016/j.htct.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Methods for blood group antigens detection: cost-effectiveness analysis of phenotyping and genotyping

Abstract: BackgroundAlloimmunization is a major problem in transfusion practice due to the clinical complications of the patients and the difficulty of choosing a unit of compatible blood product. Serological methods are widely used in blood banks, but they not always determine the phenotype. Thus, genotyping is an important complement to the serology tool as it allows one to predict the phenotype from deoxyribonucleic acid (DNA) with high accuracy.ObjectiveTo compare the centrifugation gel, microarray, Restriction Frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 20 publications
0
21
0
2
Order By: Relevance
“…PCR-SSP has been described as being more economical, relatively simple, fast, and highly sensitive and specific than other methods, ( 12 , 22 ). In our study, the standardized PCR-SSP technique showed 100% sensitivity and specificity for HLA-B heterozygous samples, as measured by the concordance of the PCR-SSP and PCR-SSOP results.…”
Section: Discussionmentioning
confidence: 99%
“…PCR-SSP has been described as being more economical, relatively simple, fast, and highly sensitive and specific than other methods, ( 12 , 22 ). In our study, the standardized PCR-SSP technique showed 100% sensitivity and specificity for HLA-B heterozygous samples, as measured by the concordance of the PCR-SSP and PCR-SSOP results.…”
Section: Discussionmentioning
confidence: 99%
“…The breathing sound recording device is a custom-made digital stethoscope assembly with an inbuilt Bluetooth module developed in an earlier study on pneumonia [44] to communicate with the smartphone for recording the breathing sounds. The stethoscope placement at the most appropriate part of the body is a critical factor [66] .…”
Section: Methodsmentioning
confidence: 99%
“…Rapid antigen tests use nasopharyngeal swabs (from the nose and throat) to collect sample fluid, and immediately detect proteins of SARS-CoV-2 [11] . At 6.16 USD, the Rapid antigen test is economical and can cater to a large population at a given time [44] . The detection method can specifically identify infectious agents while being conducted from the comfort of one’s home.…”
Section: Introductionmentioning
confidence: 99%
“…Patients from specific populations or those with unexplained complex serological results will particularly benefit from NGS analysis used as a first-line test instead of relying on extended phenotyping, multistep antibody identification and numerous single or screening genetic tests. [77][78][79] In 2014, Mazonson et al estimated the costs of pre-transfusion tests at about 195 USD per patient but for patients with autoimmune hemolytic anemia the cost increased to 1490 USD as compared to 65 USD for six blood genes when using the NGS approach. 80 3) The huge capacity of the NGS experiment makes this technology an ideal tool for mass screening of blood donors for all clinically important antigens and also to detect individuals with rare blood group antigens in various ethnic groups.…”
Section: Applications Of Ngs In Transfusion Medicinementioning
confidence: 99%